Genotoxicity of Microcystin-LR in In Vitro and In Vivo Experimental Models. (18th May 2014) - Dias, Elsa; Louro, Henriqueta; Pinto, Miguel; Santos, Telma; Antunes, Susana; Pereira, Paulo; Silva, Maria João
Abstract : Microcystin-LR (MCLR) is a cyanobacterial toxin known for its acute hepatotoxicity. Despite being recognized as tumour promoter, its genotoxicity is far from being completely clarified, particularly in organs other than liver. In this work, we used the comet and/or the micronucleus (MN) assays to study the genotoxicity of MCLR in kidney- (Vero-E6) and liver-derived (HepG2) cell lines and in blood cells from MCLR-exposed mice. MCLR treatment (5 and 20 μ M) caused a significant induction in the MN frequency in both cell lines and, interestingly, a similar positive effect was observed in mouse reticulocytes (37.5 μ g MCLR/kg, i.p. route). Moreover, the FISH-based analysis of the MN content (HepG2 cells) suggested that MCLR induces both chromosome breaks and loss. On the other hand, the comet assay results were negative in Vero-E6 cells and in mouse leukocytes, with the exception of a transient increase in the level of DNA damage 30 minutes after mice exposure. Overall, the present findings contributed to increase the weight of evidence in favour of MCLR genotoxicity, based on its capacity to induce permanent genetic damage either in vitro or in vivo . Moreover, they suggest a clastogenic and aneugenic mode of action that might underlie a carcinogenic effect.